Un contrato: Doscientos años de historicidad - Catalan, Marcos (2014)
Assuming that the passing of time is reflected in each individual, preventing its stagnation, and that all interpretations must be temporally and spatially contextualized, the contract is studied here according to its changes in the last two centuries, changes that were propelled, at first, by the transition from the Liberal state to the Welfare state and, later on, by its replacement for the Democratic state of Law.